Pricing Capital Assets in an International Setting: An Introduction - Stulz, René M. (Journal of International Business Studies, 1984)
This paper shows how differences across countries of 1) inflation rates, 2) consumption baskets of investors, and 3) investment opportunity sets of investors matter when one applies capital asset pricing models in an international setting. In particular, the fact that countries differ is shown to affect the portfolio held by investors, the equilibrium expected returns of risky assets, and the financial policies of firms.